Effect of cyber bullying on the distrust levels of preservice teachers: considering internet addiction as a mediating Variable - Cankaya, Ibrahima H.; Tan, Cetin (Elsevier Science Bv, 2011)
The aim of this study is to determine the effect of cyber bullying on the distrust levels among the final year university students by considering the intermediary effect of internet addiction. The study group comprises preservice teachers who were senior year students at the Firat University Education Faculty in Elazig city, Turkey during the spring term of 2009 2010 academic year. Cyber bullying of preservice teachers directly impacts their distrust levels at the 0.24 level. However, when internet addiction was included in the model as a mediating variable, the direct impact of cyber bullying on distrust decreased to 0.14. Therefore, it is evident that when cyber bullying is mediated by internet addiction, its impact on the distrust levels of preservice teachers is more significant. (C) 2010 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the Guest Editor.
1st World Conference on Information Technology (WCIT) -- OCT 06-10, 2010 -- Bahcesehir Univ, Istanbul, TURKEY
Keywords: Cyber bullying; distrust; internet addiction